2020
DOI: 10.3390/ijerph17165719
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Measurement Instruments for Diabetes: A Systematic Psychometric Review

Abstract: Background: Diabetes is a serious chronic disease associated with a large number of complications and an increased risk of premature death. A dietary evaluation is of utmost importance for health promotion, disease prevention and individual treatment plans in patients with diabetes. Methods: An exhaustive search was carried out in various databases—Medline, Web of Science, Open Gray Cochrane Library and Consensus-based Standards for the selection of health status Measurement Instruments (COSMIN)—for systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
2
0
2
Order By: Relevance
“…All patients completed a modified MDKT [ 21 ] at baseline and at the end of the 3-month trial. The MDKT was selected as it has been widely used in diverse populations [ 23 28 ], and because it is a quick and low-cost method of assessing general knowledge of diabetes and diabetes self-care that has previously demonstrated appropriate reliability and validity [ 21 , 22 ]. The 23-item original questionnaire was translated into Vietnamese and adapted as required on the basis of a pilot test performed in 10 people with type 2 diabetes, which resulted in one question being removed.…”
Section: Methodsmentioning
confidence: 99%
“…All patients completed a modified MDKT [ 21 ] at baseline and at the end of the 3-month trial. The MDKT was selected as it has been widely used in diverse populations [ 23 28 ], and because it is a quick and low-cost method of assessing general knowledge of diabetes and diabetes self-care that has previously demonstrated appropriate reliability and validity [ 21 , 22 ]. The 23-item original questionnaire was translated into Vietnamese and adapted as required on the basis of a pilot test performed in 10 people with type 2 diabetes, which resulted in one question being removed.…”
Section: Methodsmentioning
confidence: 99%
“…La nutrición es considerada un factor fundamental para la prevención y tratamiento de la diabetes mellitus, una alimentación balanceada en adultos mayores diabéticos disminuye el riesgo de mortalidad, principalmente en mujeres quienes tienen más frecuencia de adquirir esta enfermedad posterior a los 45 años de edad (Montagut-Martínez et al, 2020). El nivel socioeconómico se posiciona como la causa principal de un estado nutricional deficiente en los adultos mayores debido a que priorizan gastos en otros aspectos, entre ellos la compra de medicamentos y medicinas, dejando de lado una alimentación nutritiva que en ocasiones es la que genera las enfermedades (Chavarría et al, 2017).…”
Section: Discussionunclassified
“…As it is well known, the evaluation of dietary intake and physical activity is essential because it allows the development of personalized interventions focused on improving both behaviors in people with type 2 diabetes. Promoting a healthy lifestyle, including diet and physical activity, in individuals diagnosed with type 2 diabetes is essential for good outcomes and the prevention of potential complications [24]. The systematic review by Wee et al [25] highlights the importance of assessing patient-reported outcomes related to lifestyle, self-care, self-efficiency, psychosocial impact, and empowerment in this population.…”
Section: Discussionmentioning
confidence: 99%